An Investigation into the Relationship between Ethical Leadership and Organizational Commitment in Small to Medium Enterprises in India - Mendonca, Kenneth (2013)
Ethical leadership has been receiving a lot of attention lately due to the rise in scandals, corruption and disasters which are present in every organization. Many large business organizations are implementing ethical culture and searching for leaders with a moral compass to lead. However, developing countries like India, where small to medium enterprises form a significant part of the economy do not have the benefit of formal leadership and training. The research is a preliminary step in opening up avenues for research in these topics. The study reviews leadership theories along with ethical leadership and organizational commitment and then proceeds to use quantative analysis through descriptives to examine the relationship between ethical leadership and organizational commitment in small to medium industries in India. Finding in the study indicate that ethical leaders in such organizations have a positive effect on the employees which in turn boosts their performance, satisfaction and morale.